Permian adakitic magmatism in the Khanui Group, Northern Mongolia – Late Paleozoic slab-melting of subducted oceanic plate beneath the "Siberian continent". (November 2018) - Tsukada, Kazuhiro; Nuramkhaan, Manchuk; Purevsuren, Nemekhbayar; Kabashima, Taro; Kondo, Tomoyuki; Gantumur, Onon; Hasegawa, Hitoshi; Yamamoto, Koshi
Abstract: The Khanui Group, the Permian volcanic rock series of northern Mongolia, is a key geologic unit in the understanding of the Permian subduction-related magmatism at the southern margin of the "Siberian continent" (Siberian craton and accreted geologic units). Several studies have been carried out in the Khanui Group, but fundamental questions on its detailed petrogenesis remain to be answered. In this paper, the lithology, stratigraphy, zircon U-Pb age, and geochemistry of the Khanui Group in the Bulgan area of Mongolia, are described, and the Permian magmatism of the southern margin of the Siberian continent is discussed. The Khanui Group in this area is composed of intermediate lava and pyroclastic rocks. The zircons from this lava give a U-Pb age of 256.9 ± 2.2 Ma, and are thus Late Permian. The lava is 53–61 wt.% SiO2, 17 wt.% Al2 O3, low K2 O/Na2 O (avg. 0.4), high Sr/Y (avg. 97), high La/Yb (avg. 21), and comparatively high Mg# (avg. 43) which suggests that it is composed of adakites originating from subducted basaltic slab-melt. The lava is enriched in Cr and Ni compared with typical slab-melt, which likely to be the result of an interaction between the slab-melt and the overlying mantle peridotite. The Khanui rock thus confirms the existence of a basaltic slab beneath the Permian Siberian continent, and also the Late Paleozoic subduction of the Mongol-Okhotsk oceanic plate beneath the Siberian continent.